Psychosocial Characteristics and Outcomes in Patients with Left Ventricular Assist Device Implanted as Destination Therapy - Snipelisky, David (Am Heart J, 2015)
BACKGROUND: Psychosocial factors impact survival in patients undergoing cardiac transplantation, but it is unclear whether they affect outcomes in patients undergoing left ventricular assist device (LVAD) implantation as destination therapy (DT). METHODS: Patients undergoing DT LVAD at the Mayo Clinic in Rochester, Minnesota from February 2007 to December 2013 were included. Psychosocial characteristics at the time of LVAD implantation were abstracted from the medical record. Andersen-Gill and Cox models were used to examine the association between psychosocial characteristics and all-cause readmission and death, respectively. Patients were censored at death or last follow-up through September 2014. RESULTS: Among 136 patients (mean age 64 years, 17% female), most were married/living with a partner (82%), half (55%) had post-high school education, and a history of depression was common (32%). While most patients were former tobacco users (60%) only a small proportion were current tobacco users (10%), had a history of alcohol abuse (16%) or illegal drug use (7%). After a mean follow-up of 2.2 ±1.8 years, 78% of patients had been readmitted (range 0–14 per person) and 49% had died. There were no statistically significant differences in the risk of death according to psychosocial characteristics. However, current tobacco users had lower risk of readmission (adjusted HR 0.57, 95% CI 0.38–0.88), while illegal drug use (HR 1.55, 95% CI 1.01–2.35) and depression (HR 1.77, 95% CI 1.40–2.22) were associated with higher readmission risk. CONCLUSIONS: Psychosocial characteristics are not significant predictors of death, but are associated with readmission risk after DT LVAD.